-(-5+3)+4x-2*2=50

Simple and best practice solution for -(-5+3)+4x-2*2=50 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-5+3)+4x-2*2=50 equation:


Simplifying
-1(-5 + 3) + 4x + -2 * 2 = 50

Combine like terms: -5 + 3 = -2
-1(-2) + 4x + -2 * 2 = 50

Multiply -1 * -2
2 + 4x + -2 * 2 = 50

Multiply -2 * 2
2 + 4x + -4 = 50

Reorder the terms:
2 + -4 + 4x = 50

Combine like terms: 2 + -4 = -2
-2 + 4x = 50

Solving
-2 + 4x = 50

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 4x = 50 + 2

Combine like terms: -2 + 2 = 0
0 + 4x = 50 + 2
4x = 50 + 2

Combine like terms: 50 + 2 = 52
4x = 52

Divide each side by '4'.
x = 13

Simplifying
x = 13

See similar equations:

| 7x^2+21x=126 | | 8h+4h-7h-4h=18 | | 3x^2+40x-8=0 | | 7n^2=-42n+49 | | 50-13=2x-3 | | 22000000=0.3(x)+15 | | y=-.2x^2+10x+280 | | 10(x+147)=-2(5-x) | | -15x^2-20x=0 | | (5y+2)=(3y+6) | | 8x+2(0)=0 | | X^2-32-4x=0 | | 10x^2-4x-2=0 | | -12+-1x= | | (4x)=(5x-3) | | 3x^3-5x^2+48x-80=0 | | 2x+5y-6=6 | | j=12 | | 3x+y(0)=-3 | | -40m+84= | | 3-6*3+2=X | | 6j-j-2j+j=20 | | 2(5+y)=-18 | | 6w^2-54= | | 20k-14k-2=10 | | -12x+6y=8 | | 4y+2=y+2 | | 5y-4=y+2 | | -8(x+7)+60=9-9x | | 4b-14b-17=65 | | 5y-4=4y-2 | | 7r=(-5r)+144 |

Equations solver categories